The Implementation of the Project-Based Learning (PjBL) Model Supported by Digital Media in Teaching Speaking Skills at the State Islamic Senior High School 1 Klaten - Nurul Alfa Alfina; Muhammad Zaenuri; Anisatul Barokah; Sukirman Sukirman (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This study aims to explore the implementation of Project-Based Learning (PjBL) using digital media in teaching maharah kalam (speaking skills) at MAN 1 Klaten. The research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The research subjects include Arabic language teachers and students. The findings show that using digital media such as YouTube, Kahoot, Quizizz, and digital books can optimize the five main components of PjBL: fundamental questions, collaboration, product development, assessment, and reflection. The integration of digital media enhances students' creativity, collaboration, and understanding in oral communication. Additionally, digital technology provides extra motivation for students to actively participate and confidently use the Arabic language. This study concludes that digital media-based PjBL is an innovative and effective approach to language learning in the modern era. Digital media not only enriches language learning but also facilitates interaction and language practice in authentic contexts.Keywords: Speaking Skills, Digital Learning, Project-Based Learning (PJBL) مستخلص البحثتهد? هذه البحث إلى استكشا? تن?يذ التعلم القائم على المشاريع (PjBL) المستند إلى الوسائط الرقمية ?ي تعليم مهارة الكلام بالمدرسة العالية الإسلامية الحكومية 1 كلاتن استخدمت الدراسة منهجًا وص?يًا نوعيًا مع تقنيات جمع البيانات من خلال الملاحظة، والمقابلات، والتوثيق. وشملت عينة البحث معلمي اللغة العربية والطلاب.أظهرت نتائج البحث أن استخدام الوسائط الرقمية مثل YouTube و Kahoot وQuizizz والكتب الرقمية ي?مكن أن يعزز المكونات الخمسة الأساسية لـ PjBL، وهي: الأسئلة الأساسية، والتعاون، وتطوير المنتج، والتقييم، والتأمل. ساعد تكامل الوسائط الرقمية ?ي تعزيز إبداع الطلاب وتعاونهم و?همهم للتواصل الش?وي. بالإضا?ة إلى ذلك، و?رت التكنولوجيا الرقمية دا?عًا إضا?يًا للطلاب للمشاركة ال?عالة والثقة بالن?س ?ي استخدام اللغة العربية.تشير نتائج الدراسة إلى أن PjBL المستند إلى الوسائط الرقمية ي?عد نهجًا مبتكرًا و?عالًا لتعلم اللغة ?ي العصر الحديث. ?الوسائط الرقمية لا ت?ثري تعلم اللغة ?حسب، بل تسهّل أيضًا الت?اعل وممارسة اللغة ?ي سياقات واقعية.الكلمات الم?تاحية: التعلم القائم على المشاريع (PjBL)، مهارة الكلام، الوسائط الرقمية، تعلم اللغة العربية.